Insula functional connectivity in schizophrenia - Sheffield, Julia M.; Rogers, Baxter P.; Blackford, Jennifer Urbano; Heckers, Stephan; Woodward, Neil D. (Schizophrenia research, 2020)
The insula is structurally abnormal in schizophrenia, demonstrating reductions in volume, cortical thickness, and altered gyrification during prodromal, early and chronic stages of the illness. Despite compelling structural alterations, less is known about its functional connectivity, limited by studies considering the insula as a whole or only within the context of resting-state networks. There is evidence, however, from healthy subjects that the insula is comprised of sub-regions with distinct functional profiles, with dorsal anterior insula (dAI) involved in cognitive processing, ventral anterior insula (vAI) involved in affective processing, and posterior insula (PI) involved in somatosensory processing. The current study builds on this prior work and characterizes insula resting-state functional connectivity sub-region profiles in a large cohort of schizophrenia (N = 191) and healthy (N = 196) participants and hypothesizes specific associations between insula sub-region connectivity abnormalities and clinical characteristics related to their functional profiles. Functional dysconnectivity of the insula in schizophrenia is broadly characterized by reduced connectivity within insula sub-networks and greater connectivity with regions not normally connected with that sub-region, reflected in significantly greater similarity of dAI and PI connectivity profiles and significantly lower similarity of dAI and vAI connectivity profiles (p < .05). In schizophrenia, reduced connectivity of dAI correlates with cognitive function (r = 0.18, p = .014), whereas stronger connectivity between vAI and superior temporal sulcus correlates with negative symptoms (r = 0.27, p < .001). These findings reveal altered insula connectivity in all three sub-regions and converge with recent evidence of reduced differentiation of insula connectivity in schizophrenia, implicating functional dysconnectivity of the insula in cognitive and clinical symptoms.